Acute scaphoid waist fracture in the athlete - Hughes, T. B. (Clinics in Sports Medicine, 2020)
Scaphoid fractures are the most common carpal fracture and the most challenging. Although appropriately managing acute scaphoid waist fractures is a priority, it also is of primary importance to make a diagnosis acutely. Scaphoid waist fractures can occur with low-energy trauma and lead to mild symptoms. A tendency to minimize symptoms and low level of initial disability lead to delay in diagnosis. Displaced scaphoid fractures require operative intervention uniformly. Although nondisplaced fractures can heal with nonoperative treatment, management of these injuries is affected by patient demands. In high-level athletes, operative treatment of nondisplaced injuries may lead to earlier return to sport.